SETTLEMENT MEASUREMENT OF SOFT SOIL BY CLOSE RANGE PHOTOGRAMMETRY AND PARTICLE IMAGE VELOCIMETRY TECHNIQUE (Malaysian Journal of Civil Engineering, 2018)
This paper represent the result of soft soil settlement under rigid footing by a small scale physical testing. The measurement was intended to show the deformation of a soil under a design load by the use of digital imagery. Initially, the ultimate bearing capacity was determined in order to obtain the design load of the soft ground model. The settlement under the design load was measured by an image of the exposed surface of a soil model that was captured when the loading is applied to the footing and analysed by the Particle Image Velocimetry, PIV technique. At the very same time, the settlement was measured by linear vertical displacement transducer, LVDT. The settlements results by PIV and LVDT measurements were 0.18 mm and 0.35 mm respectively. The discrepancy of both measurement techniques are as LVDT was used to determine the vertical settlement occurred at the center of rigid footing. As for, the PIV approach was applied to measure the settlement of the entire soil model at 2D plane. As a conclusion, the PIV technique that used in the small scale testing helps to directly interpret the deformation behavior occurred in the ground model.